The Role of Performance Management System in Improving Corporate Financial Performance - Ibrahim, Ibrahim; Tahir, Muhammad; Ishak, Ishak; Safrida, Safrida; Machmud, Mulyana (Atestasi : Jurnal Ilmiah Akuntansi, 2023)
This study examines the role of performance management systems (PMS) in enhancing corporate financial performance. The primary focus is how effectively PMS can align employee efforts with organizational goals and its impact on economic outcomes such as ROI and profit margins. This research employs a qualitative approach with case studies of technology and financial services companies. Data was collected through in-depth interviews and analysis of company documents. This approach allows for a comprehensive understanding of PMS implementation and the contextual factors influencing it. The findings indicate that precise goal setting, continuous feedback, and fair performance evaluations are critical components of effective PMS. Contextual factors such as leadership commitment and supportive organizational culture also play a crucial role. Integrating advanced technologies like AI and data analytics significantly improves the accuracy and efficiency of performance management processes, leading to enhanced financial performance. This study significantly contributes to the performance management field by highlighting technology's importance in optimizing PMS. Business practitioners can use these findings to improve the effectiveness of PMS in their organizations. Additionally, the research guides managers to involve employees in the PMS design and offer continuous training to ensure the system operates optimally. Further research is needed to explore the long-term impact of technology integration in PMS across various industry sectors.